Rethinking the theory of money: a study of the origins, nature and function of money - Girotto, Vitor Guidorzzi [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Despite its millennial existence and the vast literature about it, money remains one of humanity’s greatest enigmas and one device of great importance for socioeconomic organization. Economic literature has provided two different explanations to the phenomenon of money: on the one hand, money is a commodity; on the other hand, a credit. The general objective of this thesis is to determine the nature of money. In that attempt, this investigation followed specific objectives: (1) to revisit, synthesize, and present two different theories of money, namely, the Theory of Commodity Money and the Theory of Credit Money, considering their main arguments regarding the origin, nature and functions of money and credit; (2) to present points of divergence among scholars associated with each theory; (3) to introduce eventual points of convergence between such theories; and (4) to analyze money by using an interdisciplinary framework. The methodological procedures followed in this thesis consisted of a bibliographic survey in Economics and other social sciences, which helped delimit the theories candidates for the study of the nature of money. Afterwards, a method for collecting and grouping things according to shared and identifiable properties was selected, aiming to reveal implicit or hidden properties of the object. Besides the regular practice of analyzing money from its functions, other properties associated with it were considered as parameters to limit the scope of this research: money, credit and debt. The selected literature was summarized and presented as part of the literature review, providing the theoretical framework for the development of the analytical part of this research, which followed mostly an inductive approach. The quest to investigate the essence of money turned out being an investigation of both the nature of credit and money, for money is credit. This conclusion has been established by integrating procedures methods and resorting to interdisciplinary studies to support that money is credit. Anthropological studies helped define the best approach method, namely induction. Regarding the procedure methods, a comparative methodology which integrated economics, history, accounting, law, and anthropology studies was employed. This interdisciplinary approach has ratified most general conclusions presented by heterodox economic literature. Credit is, first and foremost, a social and moral relation. When exercised in an economic way, as purchasing power, it creates a set of obligations. One’s credit is another’s debt. A person’s reputation became quantifiable with the establishment of a unit of account employed for registering credit/debt relations, namely, money of account. Initially, pure accounting activities are present. Currency emerged only afterwards, in connection to the emergence of organized markets, to transfer debts. When in material form, money represents a tokenized credit/debt. When in abstract form, credit represents a contractual relation between economic agents or as accounting registers. Following a circuitist approach, credit is created, circulated, and then destroyed when the debt is extinguished. Therefore, money’s sole function is that of serving as a means of payment to release one from debt. Since only a credit can liquidate a debt, the credit essence of money is, again, reinforced.

Apesar de sua existência milenar e da vasta literatura sobre o assunto, a moeda continua a ser um dos maiores enigmas da humanidade e um importante instrumento para a organização socioeconômica. A literatura econômica oferece duas explicações para tal fenômeno: de um lado, a moeda é uma mercadoria; do outro, um crédito. O objetivo geral desta tese é determinar a natureza da moeda. Para tal, esta investigação seguiu os seguintes objetivos específicos: (1) revisitar, sintetizar e apresentar duas teorias da moeda diferentes, as Teorias da Moeda Mercadoria e da Moeda Creditícia, considerando seus principais argumentos no que tange a origem, natureza e função da moeda e do crédito; (2) apresentar pontos de divergência entre acadêmicos associados a cada teoria; (3) introduzir eventuais pontos de convergência entre tais teorias; e (4) analisar a moeda através de uma perspectiva interdisciplinar. Os procedimentos metodológicos adotados na tese consistiram de um levamento bibliográfico em Economia e outras ciências sociais, que ajudaram a delimitar as teorias candidatas ao estudo da natureza da moeda. Posteriormente, buscou-se coletar e agrupar características compartilhadas e identificáveis com o objeto para revelar propriedades implícitas ou ocultas do mesmo. Além da prática habitual de analisar a moeda por suas funções, outras características associadas a ela foram consideradas como parâmetros para delimitar o escopo da pesquisa: moeda, crédito e dívida. A literatura selecionada foi sintetizada e apresentada como parte da revisão literária, oferecendo o embasamento teórico para o desenvolvimento da parte analítica desta pesquisa, fundamentada principalmente no método indutivo. A busca para investigar a essência da moeda mostrou ser também uma investigação da natureza do crédito, afinal moeda é crédito. Esta conclusão foi estabelecida através da integração de métodos de procedimento e do auxílio de estudos interdisciplinares que reforçam que moeda é crédito. Estudos antropológicos auxiliaram a definir o método indutivo como o mais adequado método de abordagem. Quanto aos métodos de procedimento, o estudo utilizou de metodologia comparada, integrando estudos em economia, história, contabilidade, direito e antropologia. Esta abordagem interdisciplinar ratificou muitas das conclusões gerais apresentadas pela literatura econômica heterodoxa. O crédito é, antes de tudo, uma relação social e moral. Quando utilizado para fins econômicos, como poder de compra, ele cria uma série de obrigações. Crédito de um é dívida de outro. A reputação de uma pessoa se torna quantificável com o estabelecimento de uma unidade de conta utilizada para registrar relação de crédito/débito, i.e., moeda-de-conta. Inicialmente, atividades contábeis puras estão presentes. A moeda circulante só surgiu depois, no contexto do surgimento de mercados organizados, para transferir dívidas. Quando na forma material, a moeda representa um token de crédito/dívida. Na forma abstrata, representa uma relação contratual entre agentes econômicos ou apenas registros contábeis. Seguindo a abordagem circuitista, o crédito é criado, circula e é destruído quando a dívida é extinta. Portanto, a única função da moeda é servir como o meio de pagamento que libera as pessoas das dívidas. Como apenas um crédito pode liquidar uma dívida, a natureza creditícia da moeda é, novamente, reforçada.
Repensando a teoria da moeda: um estudo das origens, natureza e função da moeda
Keywords: Moeda; Crédito; Dívidas; Bancos; Mercados; Money; Credit; Debt; Market; Banks